- The Correlation Between Insulin Resistance and Blood Lipids in Children : Correlation Between Insulin Resistance and Blood Lipids - xu, Xu Xu (Journal of Medical Biochemistry, 2024)
Abstract: Introduction: this work focused on correlation between insulin resistance (IR) and blood lipids (BL) in children with simple obesity as well as the intervention effects of high-intensity interval training (HIIT) in weight loss of children. Material and Method: 80 children aged 6 to 17 years with simple obesity were selected from our hospital and randomly grouped into two. Children in control (Ctrl) group underwent traditional moderate-intensity continuous training (MICT), while those in the other group received HIIT (HIIT group). After four weeks, body composition-related indicators, BL levels, and IR were measured. Results: after exercise, children in both groups possessed obvious reductions in body mass index (BMI), body fat percentage (BFP), triglyceride (TG), and homeostasis model assessment of IR (HOMA-IR), demonstrating remarkable differences in contrast to those after intervention (P
Keywords: Children with simple obesity; Insulin resistance; Blood lipids; High-intensity interval training